Sanctification of marriage, religious coping and marital adjustment of Iranian couples. (July 2021) - Fallahchai, Reza; Fallahi, Maryam; Moazenjami, Arefeh; Mahoney, Annette
This study examined cross-sectional links of the theistic and non-theistic sanctification of marriage and positive and negative religious coping with marital adjustment for 316 married Muslims (women = 157, men = 159) from Iran. Perceiving marriage to be a manifestation of God (i.e. theistic sanctification) and reflective of sacred qualities (i.e. non-theistic sanctification) as well as engaging in positive and negative religious/spiritual (r/s) coping strategies each uniquely contributed variance to marital adjustment, after controlling for each other and global indicators of devotion to Islam (e.g. frequency of prayer, religious pilgrimages, fasting, reciting the Quran), and demographic variables (e.g. education level). Specifically, theistic sanctification (β = .40), non-theistic sanctification (β = .29), and positive r/s coping (β = .56) were uniquely tied to higher marital adjustment whereas negative r/s coping was uniquely tied to lower marital adjustment theistic (β =-15) in a hierarchical regression model with all primary variables and controls entered. These findings replicate and extend prior findings on the perceived sanctity of marriage with US samples of predominantly Christians to Muslims living in the Middle East, and offer novel cross-cultural insights into the possible roles that sanctification of marriage and r/s coping may play for marital well-being for non-distressed married Muslims.